EFEK MODERASI MOTIVASI KERJA DAN JOB RELEVANT INFORMATION ATAS HUBUNGAN PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL PERANGKAT DAERAH (STUDI KASUS DIPROVINSI JAMBI) - Asmaul Husna; Hasni Yusrianti; Hidayah Aprini (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine the influence of moderating influence, work motivation and information relevant to work on the influence of influence on managerial performance of regional apparatus. The type of data used in this study is primary data with the object of research being the SKPD of the Industry and Trade Service and the Jambi Provincial Civil Service Agency. The sample for this research is 75. The sampling method uses saturated sampling method. Data retrieval technique (Direct distribution method), namely directly visiting respondents to submit or re-collect the questionnaire. Data analysis in this study used SEM (Structural Equation Modeling) with the SmartPLS software program. The results of the study state that the sensory approach has a positive and significant effect on the managerial performance of regional apparatus. The interaction between the structure of the budget setting and work motivation as a moderating variable has a negative effect on the managerial performance of regional apparatus. Then the interaction between the budget preparation structure and information relevant to work as a moderating variable has a significant negative effect on the managerial performance of regional apparatus.